2016
DOI: 10.1109/jsen.2015.2497373
|View full text |Cite
|
Sign up to set email alerts
|

Passive UWB RFID for Tag Localization: Architectures and Design

Abstract: International audienceIn the new scenarios foreseen by the Internet of Things, industrial and commercial systems will be required to detect and localize tagged items with high accuracy, as well as to monitor the level of certain parameters of interest through the deployment of wireless sensors. To meet these challenging requirements, the adoption of passive and semi-passive ultra-wideband (UWB) radio-frequency identification (RFID) appears a promising solution which overcomes the limitations of standard Gen.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…The final location of target is estimated by using the RSSI relationship between the target tag and candidate reference tags. The system design of a UWB-RFID network for tag localisation in IoT applications is presented in [80], and it is found that the architectural choice is strictly application dependent, and must account for costs, complexity, energy efficiency, backward compatibility and performance. It is evident that the architecture design is significant to the success of an RFID sensor network application.…”
Section: H Rfid Sensor Networkmentioning
confidence: 99%
“…The final location of target is estimated by using the RSSI relationship between the target tag and candidate reference tags. The system design of a UWB-RFID network for tag localisation in IoT applications is presented in [80], and it is found that the architectural choice is strictly application dependent, and must account for costs, complexity, energy efficiency, backward compatibility and performance. It is evident that the architecture design is significant to the success of an RFID sensor network application.…”
Section: H Rfid Sensor Networkmentioning
confidence: 99%
“…The main consequence is that tags are completely asynchronous. This problem can be solved by a proper design of the code and the introduction of side synchronization signals (e.g., in the UHF band) to provide a coarse synchronization, as it will be explained later [26]. To facilitate code acquisition at the receiver in [24] (quasi)-orthogonal codes allowing multiple tags operating simultaneously with limited reciprocal interference have been investigated.…”
Section: Implementations Of Uwb-rfid Systemsmentioning
confidence: 99%
“…Due to the impossibility to extract significant energy from the UWB link because of regulatory issues, a solution is to exploit the UHF band to transfer the required energy to the tag as done in Gen.2 RFID [26].…”
Section: Implementations Of Uwb-rfid Systemsmentioning
confidence: 99%
See 2 more Smart Citations